2006
DOI: 10.1063/1.2176600
|View full text |Cite
|
Sign up to set email alerts
|

On intense electron beam propagation through gas jets

Abstract: The structure of the ionization front created by an expanding high-intensity electron beam as it travels through ∼1atm gas is considered theoretically. The velocity of the front, Vf, on the order of a few 10∧9cm∕s, is determined by the electric field ionization process. When decreasing the gas density, the velocity Vf decreases relatively slowly up to some threshold, after which it starts rapidly falling. The magnitude of Vf is higher for argon than for helium. These findings are supported by experimental obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Figure 6 shows a typical simulation result of a proton image, corresponding to a maximum electrostatic field of Ϸ10 11 V / m and a fall-off distance of Ϸ10 m. Such values are in fair agreement with the expectations from theory. 9,14,17 Of course since the total deviation depends on the line integral ͐Edx, other values of the maximum field and fall-off distance can also reproduce our images. However for too-low electric fields, it is not possible to expel all the protons from the region inside the front ͑as it happens in our case as shown in Fig.…”
Section: Simulationsmentioning
confidence: 60%
See 1 more Smart Citation
“…Figure 6 shows a typical simulation result of a proton image, corresponding to a maximum electrostatic field of Ϸ10 11 V / m and a fall-off distance of Ϸ10 m. Such values are in fair agreement with the expectations from theory. 9,14,17 Of course since the total deviation depends on the line integral ͐Edx, other values of the maximum field and fall-off distance can also reproduce our images. However for too-low electric fields, it is not possible to expel all the protons from the region inside the front ͑as it happens in our case as shown in Fig.…”
Section: Simulationsmentioning
confidence: 60%
“…7,14,17 In particular, we have shown that ͑i͒ the propagation velocity and propagation distance increase with gas pressure and ͑ii͒ the propagation velocity slows down with time.…”
Section: Discussionmentioning
confidence: 97%